Social Media-Driven Microlearning: A Framework for Enhancing Student Learning Experience and Efficacy - Au, Bill (Digital Repository of Theses - SSBM Geneva, 2025)
This research explores the effectiveness of social media-driven microlearning in enhancing knowledge retention, comprehension, and academic performance among higher education students. With the increasing integration of digital tools into pedagogical practice, microlearning delivered through social media platforms offers a novel approach to addressing contemporary learning preferences and cognitive engagement challenges. The study aimed to assess the pedagogical value of microlearning when implemented within familiar social media environments, identify its key design and engagement factors, and develop a comprehensive framework to guide educators in its adoption. Four core research questions were addressed, focusing on the impact of social media-based microlearning on student outcomes, its effectiveness in meeting educational objectives, the role of content structure in shaping user experience, and the development of a strategic implementation model. A quasi-experimental design was employed, involving 614 undergraduate students from a university in Vietnam. Participants engaged with modular microlearning content delivered via a selected social media platform. Data was collected through surveys and performance assessments, and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to examine the relationships between variables such as platform familiarity, content design, engagement, comprehension, retention, student experience, and academic performance. The findings confirmed strong, statistically significant relationships among the constructs. Engagement emerged as a central mediator linking platform affordances and instructional design to learning outcomes. Comprehension and retention were positively influenced by content quality and interactivity, which in turn contributed to improved academic performance and student experience. Based on these results, a validated framework was developed to support the design, implementation, and evaluation of social media-driven microlearning initiatives. The framework offers practical guidance for educators seeking to adopt this approach, while also contributing new theoretical insights into digital pedagogy. The study concludes that microlearning delivered through social media can be an effective, scalable, and engaging educational strategy, particularly when informed by established pedagogical theories and responsive to learner needs.